The Effect of Features, Application Duration and Quality of Practice License Services on Health Worker Satisfaction - Rofiqa Marta Hamdhani; Slamet Muchsin; Rini Rahayu Kurniati (Eduvest - Journal of Universal Studies, 2025)
The Practice License (SIP) is an official acknowledgment of healthcare professionals’ competence and serves as a regulatory tool to ensure patient safety and high service standards. The addition of a submission duration feature is expected to accelerate the SIP issuance process and improve the overall quality of licensing services. This study aims to analyze the effects of submission duration and service quality on healthcare professionals’ satisfaction, both individually and simultaneously, and to determine which factor has the strongest influence. A quantitative approach was applied, using questionnaires for data collection and SPSS version 24 for data analysis. From a total population of 443 healthcare professionals who applied for a SIP via the e-Simpadu system between January 2 and October 31, 2024, a sample of 210 respondents was selected using Slovin’s formula. Multiple linear regression analysis was used. The partial test showed that submission duration (t = 16.088) and service quality (t = 9.226) both had significant effects, with t-values exceeding the critical t-table value of 1.971. Simultaneously, both variables significantly influenced satisfaction (F = 689.329 > 3.00; sig = 0.00). Among the two, submission duration was the most dominant factor, contributing 56.62% (β = 0.627), while service quality contributed 30.28%.